How the Universe Works: Part 4. Philosophical Foundations of Space Vitality: Energy, Consciousness, and the Mathematical Interpretation of the Processes in Space of Universe (London Journal of Research In Science: Natural and Formal, 2025)
Space is a material structure, a container of material objects densely enveloped in energy. The main function of space is to ensure the vitality of the Universe in the process of interaction of objects of matter on the basis of intellectual and informational support of its basis - objective reality. The task of the latter is ensuring the failure-free execution of all processes of interaction, what is the basis of the vitality of the space of the Universe as a whole. The existence and development of subjective reality on the basis of biological life on our planet is based precisely on the vitality of objective reality and the intellectual and informational properties of space. Subjective reality is the consciousness of the life process, which is created as a result of the total process of life as a whole throughout the entire period of its existence. The body in which the process of life of a certain individual takes place is a material shell of the primary vitality based on the vitality of objective reality. The main function of subjective reality of biological life is to create a product that goes beyond the capabilities of objective reality. First of all, this is the process of functioning of renewable bioenergetics based on biological synthesis, and the creation of specific technological capabilities for influencing and controlling processes in objective reality. Nature itself, possessing all the prerequisites, cannot change itself, since it is not able to create the necessary conditions for this. Nature is able to provide all the processes of creating and ensuring jet motion, but it is not able to create a jet engine. Due to this, the activity of subjective reality has radically changed the natural conditions on earth. The vital capacity of space, possessing an extremely high level of intelligence, is provided by the intellectual and informational capacity of objective reality, which is the basis of the subjective reality of the Universe. Extremely important in this context is the mathematical interpretation of energy transfer processes in space, which are mathematically described by a mathematical sequence with the performance of work. The method of mathematical analysis, which significantly expands the possibilities of mathematical interpretation of energy transfer processes, provides the opportunity of creatingan universal formula for interaction in space.
Keywords: heavy metals; Desalination; Modification; Membrane; Nanocellulose; Reusability; Water Treatment; cork oak; Quercus suber; forest decline; cork production; Mediterranean ecosystems.; space; substance & energy; vital capacity; consciousness; force interaction; work of energy; mathematical sequence.